Direito Penal Econômico e os vetores de sua aplicação - Pedroso, Fernando Gentil Gizzi de Almeida (2019)
With the evolution of the structures of the global financial market and the deterioration of other once abundant institutes, has been noticed a greater fragility of the capital scene. This fact brings to the epicenter of the world a recent deleterious (economic) reality that affects, in a single act, a plurality of individuals. In this step, a brief study of this new field of knowledge is necessary - in order to understand the solutions found to mitigate the problematic that is now uncovered and, especially, if they are able to face these deleterious contours. In order to do so, it will be necessary to readapt the principles of the Classic Penal Law, either through the creation of types of danger, open types and (im) possibility of criminal liability of legal entities